ANALISIS KECELAKAAN KERJA DENGAN PERILAKU PEKERJA DI AREA GALANGAN KAPAL - Septian Dwi Permana; Handayani Handayani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Safety-based behavior is part of the risk control process for unsafe behavior as a cause of work accidents. there are many potential hazards posed by the characteristics of the production process or material that can result in work accidents. The method used is a literature study. The data used in this study is secondary data derived from national and international scientific articles. The databases used are Google Scholar, Mendeley, Science direct and Research Gate. The results showed that age, attitude, actions, availability of facilities/facilities, work safety regulations, the role of co-workers in communication and training can affect the behavior of workers in the area of the shipyard graving dock.